Defining extended half‐life rFVIII—A critical review of the evidence. Issue 3 (6th April 2018) - Mahlangu, J.; Young, G.; Hermans, C.; Blanchette, V.; Berntorp, E.; Santagostino, E.
Abstract : Introduction: Recent haemophilia treatment advances include new recombinant FVIII (rFVIII) products with improved pharmacokinetic (PK) properties that aim to reduce the burden of prophylaxis. These treatments are commonly referred to as extended half‐life rFVIII products (EHL rFVIII). There is no uniform definition of what constitutes an EHL rFVIII. Such a definition would help physicians, patients and funders understand the properties of standard and EHL rFVIIIs and thus provide clarity when selecting an EHL in clinical settings. Aim: To critically assess the published evidence on new and emerging rFVIII products in order to propose a definition to classify EHL rFVIIIs. Methods: We systematically searched PubMed, EMBASE and regulatory authorities (FDA/EMA/Health Canada) websites for publications and regulatory submissions describing prospective crossover PK studies evaluating rFVIIIs that demonstrate improved PK parameters in adults and adolescents with severe haemophilia A. Results: Following critical analyses of the published data, we developed a holistic approach to defining rFVIIIs as EHLs, which requires all of the following: (i) using technology designed to extend rFVIII half‐life; (ii) lacking bioequivalence with a standard rFVIII comparator—above the FDA/EMA cut‐off of 125% for the 90% confidence intervals for area under the curve ratio; and (iii) having an extended half‐life ratio measured in a PK comparator crossover study. Conclusion: In this systematic review, a pragmatic definition of EHL rFVIII has been proposed that should provide better clarity in clinical discussions surrounding the appropriate use of rFVIII products. At present, only products using PEGylation or Fc fusion half‐life extension technology meet the proposed criteria for definition of EHL rFVIII.